From UNESCO to Google Maps: Analysis of Data and Visitor Impressions of Sites in Kosovo and Metohija on the World Cultural Heritage List - Mirković Maksimović, Olga D. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Transformations of various aspects of cultural heritage valuation have been occurring parallel to technological changes of the past century, with networking playing a key role in this evolutionary process. The analysis of user experiences and perceptions, and the need for their measurement and quantification, represent key aspects of the times we live in, shaped by models of heritage communication and interpretation linked with information technologies. Laurajane Smith (2010) argues that the true ownership of heritage, when our emotions and sense of belonging are genuinely engaged, lies not so much in possessing the material but in the act of transmitting and receiving memories and knowledge. Building on this, the paper illuminates the relationship between what is protected as cultural-historical value, recognized as universal under the UNESCO World Heritage Convention, and how visitors to specific sites experience and perceive these values. The sites studied in Kosovo and Metohija include the Visoki Dečani Monastery, the Patriarchate of Peć Monastery, the Gračanica Monastery, and the Church of the Virgin of Ljeviš. The research conducted, analysing data from 3772 user reviews collected via the Google Maps platform at selected locations, provides insights into whether visitors to these sites encounter the same challenges and beauties as institutional representatives, and how such knowledge can aid in the preservation of cultural heritage.